T-cell receptor gene rearrangements in functional T-cell clones from severe combined immune deficient (scid) mice: reversion of the scid phenotype in individual lymphocyte progenitors. - Petrini, J H (1990)
The severe combined immune deficient (scid) mouse mutant is characterized by a general absence of functional B and T lymphocytes. This deficiency appears to result from a defect in the variable-diversity-joining (VDJ) recombinase system, which is responsible for the assembly of V, D, and J gene segments that code for immunoglobulin and T-cell receptor (TCR) V regions. Most rearranged immunoglobulin or TCR genes in transformed scid lymphocytes contain abnormal J-associated deletions and are nonfunctional. A few functional lymphocyte clones do arise, however, in some young adult scid mice and in virtually all old scid mice; this phenomenon is referred to as leakiness. Alloreactive, CD3+ T-cell clones were isolated from leaky scid mice and the status of their TCR beta and gamma loci was examined in an effort to assess the nature of the recombinase activity that gives rise to functional scid lymphocytes. The recombination junctions of six gamma and two beta alleles were sequenced, representing four alloreactive T-cell clones. All of the junctions were indistinguishable from those seen in normal cells. These results cannot be attributed to selection by antigen because other rearranged TCR genes account for the TCR molecules expressed by these T-cell clones. We conclude that reversion of the scid phenotype can occur in rare lymphocyte progenitors and may account for most functional lymphocyte clones in leaky scid mice.